"DUAL CAREER": CASE STUDY IN ELITE SPORTS - Simona OROS; Iacob HANȚIU (Cluj University Press, 2016)
During their high performance sports career, athletes commit themselves to fulfil several roles, being at the same time students, family members or employees, being challenged to meet the requirements of a dual career: an active, sportive and educational/professional one. The timespan of a "dual career" for a sportive is a complex one and requires effort and sacrifices, as well as support from the family, school and sporting environment that should help in the achievement of a balanced development. The present endeavour is a case study which wishes to present a global image of the educational, professional formation route, developed in parallel with the high performance sports activity, all framed within the concept of "dual career". It is a qualitative research in which the interview method has been used, the analysed case being considered a model of success in high performance sports. The conclusions of this study emphasize the complexity of the phenomenon, as well as the need to responsibly manage the two careers, involving both the sportive and educational/professional formation. "Dual Career": studiu de caz în sportul de elită. De-a lungul carierei sportive de performanță, sportivii își asumă angajamentul de a îndeplini mai multe roluri, putând fi în același timp elevi/studenți, membri de familie sau angajați, fiind provocați să gestioneze cerințele unei duble cariere: sportivă și educațională/profesională. Perioada "dublei cariere" pentru un sportiv este una complexă care necesită efort și sacrificii, dar și suport al mediului familial, școlar sau sportiv care trebuie să susțină o dezvoltare echilibrată. Prezentul demers este un studiu de caz ce își propune să prezinte o imagine de ansamblu al traseului educațional, de formare profesională, dezvoltat în paralel cu activitatea sportivă de performanță, încadrat sub conceptul de "dublă carieră". Este o cercetare calitativă în care s-a folosit metoda interviului, cazul analizat fiind considerat un model de reușită în sportul de înaltă performanță. Concluziile acestui studiu scot în evidență complexitatea fenomenului, dar și nevoia de gestionare cu responsabilitate a celor două cariere - sportivă și educațională/formare profesională.  Cuvinte-cheie: dublă carieră, sport de performanță, sportiv de elită, educație, formare profesională